Age-Related Changes in Adult Muscle Morphology - C. Kostek, Matthew; J. Delmonico, Matthew (Current Aging Science, 2011)
Skeletal muscle undergoes numerous morphological changes from early adulthood to old age including muscle size, configuration, and structure. This review discusses these changes, considers the limitations in interpreting studies, addresses the potential health implications, and describes some mechanisms and interventions to ameliorate aging-related changes in skeletal muscle. Discussion in each section focuses on measurement and analysis techniques of muscle morphology, limitations of human research, and the discussion uses animal work to support findings in humans. We examine the discrepancies in the study of fiber type distribution with age, and special emphasis is given to two topics: fiber-type distribution and intra- and intercellular fat. Finally, training adaptations and health implications are briefly discussed. The focus of the current review is the morphological changes that occur in skeletal muscle during the normal aging process, with emphasis on human studies.
Keywords: pennation